Mobilbetalinger - Jesper Bakkegaard (Danmarks Nationalbank, 2009)
– The mobile phone can now be used as a payment instrument to purchase goods and services. Several factors have supported this use of mobile phones. Firstly, the mobile phone has a market penetration close to 100 per cent. Secondly, technological developments have enabled new payment services to mobile phones and expanded the range of goods and services that can be purchased by means of a mobile phone. Thirdly, payments made by mobile phones - known as mobile payments - are in many contexts a more simple and faster way of making payments than other payment methods. The volume of mobile payments is still relatively limited in Denmark. However, pilot projects have shown that consumers are willing to use their mobile phones for payments. Yet, Denmark is still lagging behind several countries when it comes to mobile payments. This applies especially to the so-called proximity payments where the mobile phone is used instead of cash and/or payment cards for point of sales transactions.
Keywords: 330; Mobiltelefon; Zahlungsverkehr; Dänemark